Correction: Saudi women's leadership experiences in the healthcare sector: A qualitative study. - Abbas Al Mutair; Muna Al-Ghuraibi; Yasmine Alabbasi; Fatemah Alghadheeb; Alexander Woodman; Alya Elgamri (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0285187.].